'n Projekbestuurdersprofiel vir die konstruksiebedryf - Archer, Mart-Mari (University of the Free State, 2011)
Project managers within the construction industry possibly have a lack of sufficient and effective management skills. This study aims to find solutions, and to propose a model with guidelines for creating a profile for effective project management, as well as to determine the characteristics and skills needed by a project manager. Basic management principles, tasks, responsibilities and behaviour of the project manager are researched and these results may form the basis for creating of a probable profile for a construction project manager. If a profile can be created based on the research, this profile might be used to prepare the project manager for effective management and the successful completion of projects. Construction project managers can be measured by means of this profile and adapt where necessary to meet the requirements. Gaps that are thus identified can be rectified. This profile can form the basis of model proposing to measure the maturity of the profile for the construction project manager in construction project management companies. Individuals will also be able to evaluate themselves and to adapt where necessary. The research shows regular cooperation between project managers in the construction industry and other stakeholders, and that poor management by the project manager contributes to project failure. Although management guidelines exist, it is evident that project managers do not implement them effectively. This has a possible negative impact on the projects. It is important that the project manager has some characteristics and skills to successfully implement management functions. When a construction project is undertaken, timely identification of tasks and activities, management areas, functions and responsibilities is important in order for the project manager to be knowledgeable about what is expected. The areas of management, the functions and responsibilities of the project manager can be regarded as the task of the project manager, while certain skills and characteristics can assist the project manager to successfully perform the necessary management tasks. The profile for a project manager is compiled by identifying the tasks (management areas, functions and responsibilities) and the aids (skills and characteristics) needed for the successful execution of the task.

Projekbestuurders binne die konstruksiebedryf het moontlik ‘n gebrek aan doeltreffende bestuursvaardighede. Hierdie studie poog om oplossings te vind en om ŉ model met profielriglyne vir doeltreffende projekbestuur voor te stel, asook om die eienskappe en vaardighede waaroor die projekbestuurder moet beskik, te bepaal. Basiese bestuursbeginsels, pligte, verantwoordelikhede en gedrag van die projekbestuurder word ondersoek en hierdie inligting kan die basis vorm vir die moontlike profiel vir konstruksieprojekbestuurders. Indien ŉ profiel daargestel kan word, gebaseer op die ondersoek, kan hierdie voorgestelde profiel moontlik die projekbestuurder voorberei vir doeltreffende projekbestuur en suksesvolle projekvoltooiing. Konstruksieprojekbestuurders kan aan hierdie profiel gemeet word en die nodige aanpassings maak om daaraan te voldoen. Moontlike leemtes kan deur so ŉ profiel geïdentifiseer en reggestel word. Hierdie profiel kan neerslag vind in ŉ voorgestelde model om die volwassenheid van die profiel vir die konstruksieprojekbestuuder in ŉ konstruksieprojekbestuursmaatskappy te meet. Individue kan dit ook gebruik om hulself te evalueer en dienooreenkomstige aanpassings aan te bring. Die ondersoek toon gereelde samewerking tussen projekbestuurders in die konstruksiebedryf en ander betrokke aandeelhouers, en dat gebrekkige bestuur deur die projekbestuurder bydra tot projekmislukking. Alhoewel daar bestuursriglyne vir die projekbestuurder bestaan, is daar aanduidings dat projekbestuurders dit nie effektief toepas nie. Dit het ‘n moontlike negatiewe impak op projekte. Dit is belangrik dat die projekbestuurder oor sekere vaardighede en eienskappe beskik om bestuursfunksies suksesvol toe kan toepas. Wanneer ŉ konstruksieprojek aangepak word, is vroegtydige identifikasie van take en aktiwiteite, bestuursareas, -funksies en -verantwoordelikhede belangrik sodat die projekbestuurder ingelig sal wees van wat verwag word. Die areas van bestuur, die funksies van die konstruksieprojekbestuurder en die verantwoordelikhede van die projekbestuurder kan as die taak wat deur die projekbestuurder verrig moet word, gesien word, terwyl sekere vaardighede en die eienskappe die projekbestuurder help om bestuurstake suksesvol uit te voer. Die profiel vir ‘n projekbestuurder word saamgestel deur die identifikasie van take (bestuursareas, funksies en verantwoordelikhede) en die hulpmiddels (vaardighede en eienskappe) om die taak suksesvol uit te voer.
Dissertation (M.Sc. (Quantity Surveying and Construction Management))--University of the Free State, 2011
Keywords: Construction projects; Project managers; Characteristics; Skills; Responsibilities; Management functions; Management areas; Project manager profile; Construction industry; Construction project management